• sartalon@lemmy.world
        link
        fedilink
        arrow-up
        0
        ·
        5 hours ago

        X^3 = x•x•x

        X^2 = x•x

        X^1 = x

        X^0 = 1

        X^-1 = 1/x

        X^-2 = 1/(x•x)

        X^-3 = 1/(x•x•x)

        When the exponent is between -1 and 1, it becomes a root function:

        X^(1/2) = sqrt(x)

        X^(1/3) = cubic root(x)

        X^-(1/2) = 1/(sqrt(x))

        X^-(1/3) = 1/(cubic root(x))

        • JPAKx4@lemmy.blahaj.zone
          link
          fedilink
          arrow-up
          0
          ·
          3 hours ago

          Oh I misunderstood the original comment, the teacher said it wasn’t the same, but it is the same. My understanding is that sqrt(x) = x^1/2